مخاطر الربا و معالجته في الإسلام - صالح، ضياء الدين عبدالله محمد (ديوان الوقف السني - مركز البحوث والدراسات الاسلامية, 2013)
Islam considered the usury one of the most dangerous financial topic which effects to the individual and the society, so the punishment of it was the deprivation of Allah mercy (Allah will deprive Usury of all blessing But will give increase For deeds of charity) Al Baqarah (276), Islam clearly stood against all kind of usury whatever it was, where Islam encourage good, charity and Zakat,, where they have great benefit to people.
Keywords: الربا -- الشريعة الإسلامية -- الإقتصاد الإسلامي